2012
DOI: 10.1080/00036846.2010.511993
|View full text |Cite
|
Sign up to set email alerts
|

Testing the validity of the Feldstein–Horioka puzzle for Australia

Abstract: This paper presents an investigation into the relationship between investment and savings in Australia over the period . Using four time series techniques our results reveal that the Feldstein-Horioka puzzle exists in a weak form with a lower saving retention coefficient. Granger Causality tests illustrate that savings Granger cause investment both in the short and long runs. Our results suggest Australia could effectively adopt policies that focus on increasing investment through increasing domestic savings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Descriptive statistics is presented in Table 1.From the six plots in Appendix 0 we can see that savings and investment are I (1) variables and heteroscedasticity and normality is not a problem. Here it should be noted that even though we expect F-H coefficient 8 to be between 0 and 1, there are some deviations from this range, which implies that this model describes very simplified behaviour of savings and investment. P-value is probability of significance of this coefficient.…”
Section: Empirical Literature Reviewmentioning
confidence: 77%
See 1 more Smart Citation
“…Descriptive statistics is presented in Table 1.From the six plots in Appendix 0 we can see that savings and investment are I (1) variables and heteroscedasticity and normality is not a problem. Here it should be noted that even though we expect F-H coefficient 8 to be between 0 and 1, there are some deviations from this range, which implies that this model describes very simplified behaviour of savings and investment. P-value is probability of significance of this coefficient.…”
Section: Empirical Literature Reviewmentioning
confidence: 77%
“…Result is represented in the following aaplot 7 Standard deviations of interest rate 8 Feldstein Horioka coefficient measures capital mobility.The higher this coefficient is means that capital is less mobile in that country or countries, the lower this coefficient is it is interpreted as capital mobility. 9 Euribor and LIBOR are comparable base rates.…”
Section: Studymentioning
confidence: 99%
“…The first group of studies have followed the time series estimation route through using the country-specific time series techniques. Among them, we can highlight contributions by Miller (1998), Alexakis and Apergis (1992), Argimon and Roldan (1994), Ghosh (1995), Goldberg et al (1995), Coakley et al (1996), Jansen (1996), Liu and Tanner (1996), Hussein (1998), Kim (2001), Schmidt (2003), Hoffmann (2004) and Kumar et al (2012). These studies provide evidence of non-stationarity in ITY and STY i.e.…”
Section: Introductionmentioning
confidence: 92%
“…Grier et al (2008) using Perron (1998, 2003) structural breaks methods analysed US data from 1947 to 2007 and found a positive relationship in the short run but no cointegration between the two variables. Kumar et al (2012) analysed the savings investment relationship for 4794 C. P. Barros and L. A. Gil-Alana Australia from 1960 to 2007 with Granger causality tests and concluded that there is a positive relationship in both the short-and the long-run behaviour. Bai and Zhang (2010) analysed the Feldstein-Horioka puzzle with Financial Frictions and concluded that to solve the Feldstein-Horioka puzzle, the model needs to limit the capital flows much lower than those in the original data, and to restrict capital flows to the observed level.…”
Section: Literature Surveymentioning
confidence: 98%